2 A × 2 A × 2 A = ( ( A × A A × A × A × A ÷ 2 ) ÷ 3 ) × C = A × A
Solve for A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 2 A ) ( 2 A ) ( 2 A ) = A ⋅ A 8 A 3 = A 2 8 A = 1 A = 8
Solution- So to solve for C we discover that (A(squared)/2)/3 x C= A squared based on that we know that 2 x 3=C as (A(squared)/2)/3 x C= Equals the exact same thing the equation started with. So C=6 Now lets solve for A (A/2)(cubed)= A(squared), whelp the answer is 8!!! as we divide 8 into 2 we get 4. 4(squared)= 8(squared) divided by 4, This occurs with all numbers (check the equation below). So based on that 8 is the only number that has 8/2 (cubed)=8(squared),
equation X= b/f, B(squared)=f(squared) times x(squared), X(squared)=B(squared)/ f (squared) .
Problem Loading...
Note Loading...
Set Loading...
The above equation can be simplified into:
8 A 3 = 6 A 2 ⋅ C = A 2
which C = 6 and A 3 − 8 A 2 = 0 ⇒ A = 0 , 8 . But, A = 0 leads to division-by-zero (not allowed). So, A = 8 is the answer.